Mamu-A*01/K(b) Transgenic and MHC Class I Knockout Mice as a Tool for HIV Vaccine Development - Li, Jinliang (2009)
We have developed a murine model expressing the rhesus macaque (RM) Mamu-A*01 MHC allele to characterize immune responses and vaccines based on antigens of importance to human disease processes. Towards that goal, transgenic (Tg) mice expressing chimeric RM (α1 and α2 Mamu-A*01 domains) and murine (α3, transmembrane, and cytoplasmic H-2K(b) domains) MHC Class I molecules were derived by transgenesis of the H-2K(b)D(b) double MHC Class I knockout strain. After immunization of Mamu-A*01/K(b) Tg mice with rVV-SIVGag-Pol, the mice generated CD8(+) T-cell IFN-γ responses to several known Mamu-A*01 restricted epitopes from the SIV Gag and Pol antigen sequence. Fusion peptides of highly recognized CTL epitopes from SIV Pol and Gag and a strong T-help epitope were shown to be immunogenic and capable of limiting an rVV-SIVGag-Pol challenge. Mamu-A*01/K(b) Tg mice provide a model system to study the Mamu-A*01 restricted T-cell response for various infectious diseases which are applicable to study in RM.